134 MR Augmented Cardiopulmonary Exercise Testing – a Novel Way of Assessing Cardiovascular Function. (6th June 2015) - Ako, Emmanuel; Barber, Nathaniel; Kowalik, Grzegorz; Walker, Malcolm; Muthurangu, Vivek; Steeden, Jennifer
Abstract : Introduction: Reduced exercise capacity is a common feature of many cardiovascular diseases. Quantitative assessment of exercise capacity is usually achieved by measuring peak oxygen consumption (VO2 ). However, measuring peak VO2 alone neglects the different components of reduced exercise capacity: namely reduced cardiac output (CO) and oxygen extraction (ΔcO2 ). A better approach would be to simultaneously measure VO2 and CO and then calculate ΔcO2 . This could be achieved using MR augmented cardiopulmonary exercise testing (MR-CPET). The aims of this study were to demonstrate: 1) MR-CPET is feasible and well tolerated, 2) peak VO2 in the MR scanner correlates with conventional peak VO2 and 3) variation in peak VO2 is related to both peak CO and peak oxygen extraction (ΔcO2 ) as calculated by the Fick equation. Method: 17 healthy volunteers (21–55 years) underwent MR-CPET. Exercise was performed on an MR-compatible ergometer (Lode, Groningen, The Netherlands) and VO2 was assessed using a commercial respiratory gas analyser (Ultima, MedGraphics, St. Paul, USA) with a modified sampling tube that was MR compatible. Set-up for MR-CPET is shown in Figure 1 . Aortic flow was continuously measured using a previously validated UNFOLD-SENSE spiral PCMR sequence. Images were reconstructed using a graphical processing unit card and analysed using an in-house plug-in for OsiriX software. Conventional CPET was also performed within 2 weeks of MR-CPET. For both tests, participants were asked to rate i) concern ii) comfort and iii) perceived helplessness. Results: 15 out of 17 volunteers completed exercise; exclusions were due to claustrophobia (n = 1) and inability to master exercise technique (n = 1). Reported concern and discomfort was higher with MR-CPET, although still within acceptable limits. Peak VO2, peak VCO2 and VE showed strong correlation between conventional CPET and MR-CPET: VO2 peak (r = 0.94, p < 0.001); VCO2 (r = 0.87, p < 0.001); VE (r = 0.88, p < 0.001). Resting and peak values VO2, CO, HR, SV and ΔcO2 are shown in Table 1 . Multiple linear regression analysis demonstrated that both peak CO and ΔcO2 were independent predictors of peak VO2 measured during MR-CPET (beta = 0.73 and 0.38 respectively, p < 0.001) and conventional CPET (beta = 0.78 and 0.28 respectively, p < 0.001). Conclusion: MR-CPET is feasible, well tolerated and demonstrates physiology not apparent with conventional CPET. In this study, we have shown that MR-CPET allows assessment of the differing contributions of CO and ΔcO2 to variation in peak VO2 . We believe that will be useful in understanding the origin of reduced exercise capacity in cardiac disease.